2001
DOI: 10.1002/cne.1424
|View full text |Cite
|
Sign up to set email alerts
|

Chemical coding and electrophysiology of enteric neurons expressing neurofilament 145 in guinea pig gastrointestinal tract

Abstract: Electrophysiologic recording and indirect immunofluorescence were combined to study localization of the medium-sized neurofilament 145 (NF145) component of the cytoskeleton in morphologically identified neurons in the myenteric and submucosal plexuses of the guinea pig enteric nervous system. Neuronal localization of chemical markers, including calbindin DK28, calretinin, nitric oxide synthase, choline-acetyltransferase, neuropeptide Y, serotonin, neurokinin 1 receptor protein, and somatostatin, was integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
6
13
2
Order By: Relevance
“…In marked contrast, two previous studies found that type II neurons in the guineapig enteric nervous system were not NF-immunoreactive (Costa et al 1996;Hu et al 2002), although other neurons with NF immunoreactivity were reported in both studies. The antibodies used in one of the studies were effective in revealing neurons containing NF-M and NF-H in the central nervous system (Costa et al 1996), whereas the other study involved the use of anti-NF-M antibodies to investigate myenteric neurons (Hu et al 2002). In the present work, we have utilised antibodies shown to be effective in other species in order to re-investigate the ability of anti-NF antibodies to label type II neurons in the guinea-pig small intestine.…”
Section: Introductioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In marked contrast, two previous studies found that type II neurons in the guineapig enteric nervous system were not NF-immunoreactive (Costa et al 1996;Hu et al 2002), although other neurons with NF immunoreactivity were reported in both studies. The antibodies used in one of the studies were effective in revealing neurons containing NF-M and NF-H in the central nervous system (Costa et al 1996), whereas the other study involved the use of anti-NF-M antibodies to investigate myenteric neurons (Hu et al 2002). In the present work, we have utilised antibodies shown to be effective in other species in order to re-investigate the ability of anti-NF antibodies to label type II neurons in the guinea-pig small intestine.…”
Section: Introductioncontrasting
confidence: 57%
“…Anti-NF antibodies are also ideal for the localisation of type II neurons in cattle (Balemba et al 1999), sheep (Mazzuoli et al 2007) and mice (Qu et al 2008). In marked contrast, two previous studies found that type II neurons in the guineapig enteric nervous system were not NF-immunoreactive (Costa et al 1996;Hu et al 2002), although other neurons with NF immunoreactivity were reported in both studies. The antibodies used in one of the studies were effective in revealing neurons containing NF-M and NF-H in the central nervous system (Costa et al 1996), whereas the other study involved the use of anti-NF-M antibodies to investigate myenteric neurons (Hu et al 2002).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Immunoreactivity for a specific medium weight form (NF145) was observed within numerous fibers coursing through internodal fiber tracts and within a small population of filamentous and Dogiel type I neurons in the myenteric plexus, similar to those previously described by Hu et al (2002). Immunoreactivity Fig.…”
Section: Nf145 Labelingsupporting
confidence: 48%
“…At least three distinct classes of cholinergic descending interneurons are present in the ileum: one class is immunoreactive for serotonin (5-HT; Costa et al 1996), one class contains somatostatin (SOM; Song et al 1997), and one class contains vasoactive intestinal peptide (VIP; Steele et al 1991;. All 5-HT-immunoreactive and most SOM-immunoreactive myenteric neurons express the neurofilament subunit NF145 (Hu et al 2002). In our study, Na v 1.2 rarely co-localizes with NF145 in the ileum suggesting Na v 1.2 is not expressed by descending cholinergic interneurons containing 5-HT or by most containing SOM.…”
Section: Discussionmentioning
confidence: 99%